An adolescent with large cell calcifying sertoli cell tumor of the testis and undiagnosed Carney Complex: A case report. Issue 7 (9th March 2017) - Rosenblum, Frida; Koenig, Richard Gabriel; Mikhail, Fady M.; Porterfield, John R.; Nix, Jeffrey W.; Eltoum, Isam‐Eldin A.
Abstract : Carney Complex (CNC) is a rare autosomal dominant condition with characteristic clinical presentation, tumor development, and unique genetic mutation. We present a unique case and literature review of CNC in which two neoplasms characteristic of this complex were initially diagnosed through cytological fine needle aspirate specimens, leading to the identification of CNC, with subsequent surgical and cytogenetic confirmation. Diagn. Cytopathol. 2017;45:634–639. © 2017 Wiley Periodicals, Inc.